THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND SERVICE QUALITY CONCERNING CUSTOMER LOYALTY OF PENYET KUAH AT TIMOHO FOOD COURT, TEMBALANG SEMARANG CITY - Nuryan Dimas Maulana; Dinalestari Purbawati (Universitas Diponegoro, 2017)
Timoho Food Court is a company engaged in the field of culinary services with a variety of varieties menu of penyet. But in reality not all consumers are loyal in choosing Timoho Food Court as the main choice. Factors of product quality, price, and quality of service allegedly have a close influence on the level of customer loyalty in Timoho Food Court.This study aims to find out how the effect given by product quality (X1), price (X2), and service quality (X3) to customer loyalty penyet kuah Timoho Food Court. The type of research used is the type of explanation. The sample number is 100 respondents using purposive sampling technique. Data collection using questionnaire with Likert measurement scale. Data analysis method used is test of validity and reliability, correlation coefficient, regression test, coefficient of determination, significance of t test and F test. Based on the results of the study, three variables have been tested in stages and together show a positive and sidnificant influence on customer loyalty. The value of the variable (X1), t count (3.811)> t table (1.660), (X2) t count (3.607)> t table (1.660), (X3) t count (2.777)> t table (1.660). Significantly, the three variables are influential porsitif indicated by the value of F count of (7.971) greater than F table of (2.70). Suggestions that can be given to improve customer loyalty related to product quality, which is to add the menu variation, provide moderate portion, and maintain product hygiene. Related to the price, which is to keep the price increase to remain affordable for the consumer, as well as related to the quality of service that is to increase the number of menu list and the price of penyet kuah in the form of brochures, and add or complement the existing basic facilities.